Cerebral cavernous malformation: new molecular and clinical insights. Issue 9 (29th March 2006) - Revencu, N; Vikkula, M
Abstract : Cerebral cavernous malformation (CCM) is a vascular malformation causing neurological problems, such as headaches, seizures, focal neurological deficits, and cerebral haemorrhages. CCMs can occur sporadically or as an autosomal dominant condition with variable expression and incomplete penetrance. Familial forms have been linked to three chromosomal loci, and loss of function mutations have been identified in the KRIT1/CCM1, MGC4607/CCM2, and PDCD10/CCM3 genes. Recently, many new pieces of data have been added to the CCM puzzle. It has been shown that the three CCM genes are expressed in neurones rather than in blood vessels. The interaction between CCM1 and CCM2, which was expected on the basis of their structure, has also been proven, suggesting a common functional pathway. Finally, in a large series of KRIT1 mutation carriers, clinical and neuroradiological features have been characterised. These data should lead to more appropriate follow up, treatment, and genetic counselling. The recent developments will also help to elucidate the precise pathogenic mechanisms leading to CCM, contributing to a better understanding of normal and pathological angiogenesis and to the development of targeted treatment.